2023
DOI: 10.1093/hr/uhad019
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated SNAC9 mutants reveal the positive regulation of tomato ripening by SNAC9 and the mechanism of carotenoid metabolism regulation

Abstract: NAC transcriptional regulators are crucial for tomato ripening. Virus-induced gene silencing (VIGS) of SNAC9 (SlNAC19, Gene ID: 101248665) affects tomato ripening, and SNAC9 is involved in ethylene and abscisic acid (ABA) metabolic pathways. However, the function of SNAC9 in pigment metabolism in tomatoes remains unclear. This work seeks to discover the mechanism of SNAC9 involvement in pigment metabolism during tomato ripening by establishing a SNAC9 knockout model using CRISPR/Cas9 technology. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Liu et al [30] found that the most important function of PSY1 in peppers was to provide precursors for downstream carotenoid synthesis by regulating phytoene accumulation, rather than directly participating in pigment synthesis. Yeast one-hybrid experiments demonstrated that SINAC9 interacted with PSY1 at the protein level, affecting the chlorophyll degradation and carotenoid synthesis of tomatoes [21,70]. This study similarly found that silencing CA12g04950 had markedly different effects on PSY and CCS.…”
Section: Transcription Factors and Carotenoidsupporting
confidence: 57%
See 1 more Smart Citation
“…Liu et al [30] found that the most important function of PSY1 in peppers was to provide precursors for downstream carotenoid synthesis by regulating phytoene accumulation, rather than directly participating in pigment synthesis. Yeast one-hybrid experiments demonstrated that SINAC9 interacted with PSY1 at the protein level, affecting the chlorophyll degradation and carotenoid synthesis of tomatoes [21,70]. This study similarly found that silencing CA12g04950 had markedly different effects on PSY and CCS.…”
Section: Transcription Factors and Carotenoidsupporting
confidence: 57%
“…Knocking out NOR-like1 by CRISPR/Cas9 led to a decrease in ethylene content in tomato fruit, subsequently changing the expressions of carotenoid genes such as DXS, GGPP2, PSY1, and PSY, thereby affecting fruit color [68,69]. Research by Feng et al [70] demonstrated that silencing the SINACs of tomato led to a decrease in ethylene content and lycopene content, resulting in yellow fruit. The expressions of carotenoid genes (PSY1, DXS2, SGR1, CrtR-b2) in the SINAC9 mutant changed significantly, affecting the transformation process of chloroplasts and chromosomes.…”
Section: Transcription Factors and Carotenoidmentioning
confidence: 99%
“…In previous research, the SNAC9 gene was knocked out thoroughly using CRISPR/Cas9, resulting in an absence of expression of the protein. This led to a significant reduction in lycopene and total carotenoid contents in the mutants, possibly due to the direct regulation of key genes involved in carotenoid biosynthesis, such as PHYTOENE SYNTHASE 1 ( PSY1 ) Solyc03g031860 [ 137 ]. A strategy using NGTs has recently been implemented to rapidly generate tomato lines with fruits of varying colors [ 135 , 138 , 139 ].…”
Section: Gene Editing In Tomato Breedingmentioning
confidence: 99%
“…Researchers propose that NAC TFs form a distinct family in plants (Feng et al, 2023). NAC proteins are generally no more than 400 amino acids in length.…”
Section: Introductionmentioning
confidence: 99%
“…NOR-like 1 serves as a crucial player in the mature network, acting as a positive activator in tomato. Meanwhile, researchers also demonstrated that SlNAC9 knockout caused delayed fruit ripening and directly regulated SGR1, DXS2, PSY1 and CrtR-b2 to suppress the relative expression of carotenoid metabolism-associated genes (Feng et al, 2023). However, SlNAC1 was identified to suppress fruit ripening by regulating the promoter regions of ethylene and lycopene synthesis-associated genes (Ma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%